Reinforcement Level: An Analysis Teacher in Junior High School Teacher - Citra Maulidia; Herman Nirwana; Marlina Marlina (Universitas Negeri Padang, 2021)
The implementation of the learning process cannot be separated from the existence of the teacher. The creation of an effective learning atmosphere requires a close relationship between teachers and students. The reinforcement given by the teacher affects the level of student activity and participation in the learning process. In schools, there are still teachers who are not appropriate to implement reinforcement. This can be seen in the poorly educated treatment of teachers towards students, such as yelling at students in public, and negative labeling of students.The purpose of this study was to describe the level of reinforcement of subject teachers in Padang City Junior High School. This research uses a quantitative descriptive approach. The research sample consisted of 149 students who were taken using the purposive random sampling technique. The instrument used was the